Methods of Qur’anic memorisation (Hifz): implications for learning performance - Dzulkifli, Mariam Adawiah; Solihu, Abdul Kabir Hussain (IIUM Press, 2018)
Memorisation of the Qur’ān occupies a central position in Muslim conception of religious education. The awareness of preserving the Qur’ān through memorisation (ḥifẓ) is becoming prevalent and is still continued in these modern days in many educational institutions in many parts of the Muslim countries. This article examines different methods of Qur’ānic memorisation being practiced in Malaysia. Similarities and uniqueness of those methods will be presented. The evaluation of those Qur’ānic memorisation techniques brings to the foreground the educative value of memorisation as a learning tool and the implications memorisation methods have in enhancing an individual’s learning performance.